Validation of the Malay version of the p-QOL questionnaire - Dasrilsyah, Rima Anggrena; Ng, Beng Kwang; Atan, Ixora Kamisan; Khong, Su Yen; Nusee, Zalina; Lim, Pei Shan (Springer, 2021)
Introduction: This study aimed to translate and validate the P-QOL questionnaire in the Malay language. Methods: The P-QOL questionnaire was translated into the Malay language and subsequently back-translated to English. Test-retest reliability and internal consistency were tested. All patients who visited the gynecology outpatient clinic of UKMMC, UMMC and IIUM between January 2016 and May 2017 completed the P-QOL questionnaires and were assessed for POP-Q staging. Results: One hundred twenty patients with symptomatic pelvic organ prolapse and 180 asymptomatic patients were included. The Cronbach’s alpha for each domain was > 0.70, which confirmed that there was a highly acceptable internal consistency. The value varied between 0.88 (role limitation) and 0.912 (sleep/energy). Test-retest reliability showed a significant correlation between the total scores for each domain (p < 0.001). There was a significant correlation between P-QOL domain scores and vaginal examination findings (POP-Q). With a higher POP-Q stage, a higher impact on the quality of life was detected in symptomatic patients. The total scores from all domains were significantly higher in symptomatic patients. Conclusion: The Malay translated version of the P-QOL questionnaire is a reliable, consistent, and valid instrument for assessing the severity of the symptoms and impact on the quality of life among women with uterovaginal prolapse. It is easily understood, administered, and self-completed by patients.